2019
DOI: 10.3390/su11113033
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Production of Sweet Sorghum as a Bioenergy Crop Using Biosolids Taking into Account Greenhouse Gas Emissions

Abstract: Currently, little data are available on greenhouse gas (GHG) emissions from sweet sorghum production under temperate climate. Similarly, information on the effect of bio-based waste products use on the carbon (C) footprint of sorghum cultivation is rare in the literature. The aim of this study was to evaluate the agronomical and environmental effects of the application of biosolids as a nitrogen source in the production of sweet sorghum as a bioenergy crop. The yield of sorghum biomass was assessed and the GHG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Glab and Sowinski focused on evaluating how sewage sludge and digestate application affect the Carbon footprint of sorghum production, compared with conventional fertilization management. The study concluded that the replacement of synthetic N fertilizers by alternative nutrient sources, such as sewage sludge and digestate resulted in lower GHG emissions and are a promising strategy for low carbon in agriculture [48].…”
Section: Discussionmentioning
confidence: 99%
“…Glab and Sowinski focused on evaluating how sewage sludge and digestate application affect the Carbon footprint of sorghum production, compared with conventional fertilization management. The study concluded that the replacement of synthetic N fertilizers by alternative nutrient sources, such as sewage sludge and digestate resulted in lower GHG emissions and are a promising strategy for low carbon in agriculture [48].…”
Section: Discussionmentioning
confidence: 99%
“…As an alternative nutrient source, ADD contributes to the mitigation of climate change through the reduction of greenhouse gas emissions, both directly (Hao et al, 2016) and indirectly through the production of nitrogenous mineral fertilizers. A system integrating production of biogas and electricity from renewable sources as agro-energy crops (silage sorghum) together with animal husbandry waste (manure) with production of this silage on marginal land using digestate from AD process as soil amendment leading to approaching low carbon agriculture and circular economy by recycling nutrients (Głab et al, 2019).…”
Section: Sorghum Biogas Yieldmentioning
confidence: 99%
“…The materials for the study were forages of different sorghum varieties from an experimental plot in Pawlowice (51 • [20]. The plants reach heights of 250-350 cm.…”
Section: Plant Materialsmentioning
confidence: 99%